2009
DOI: 10.1103/physrevc.79.054605
|View full text |Cite
|
Sign up to set email alerts
|

Long-termα- and spontaneous fission measurement of aRf/et al.

Abstract: Results from long-term measurements of a chemically separated Db/Rf sample prepared from the products of a 48 Ca on 243 Am irradiation are presented. The sample with the highest spontaneous fission activity out of eight samples produced in the course of chemical experiments performed in 2004 was selected for these measurements. We conclude that there is no evidence for SF-decay originating from heavy actinide isotopes in this sample. Hence, it is appropriate to assign the SF-events observed in this experiment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…No evidence for contamination with actinides was found in a long-term post examination of the sample with the highest observed SF-event rate [6] proving that the selected separation system worked proper and reliable.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…No evidence for contamination with actinides was found in a long-term post examination of the sample with the highest observed SF-event rate [6] proving that the selected separation system worked proper and reliable.…”
Section: Discussionmentioning
confidence: 90%
“…This experiment -although accepted as the first independent prove of the synthesis of superheavy elements in 48 Ca induced nuclear reactions -had two weak points: (a) -spectra had not been shown, due to the high -background rendering impossible the identification of a possible actinide contamination and (b) no differentiation between Db and Rf could be made because of their similar behavior in the selected chemical separation system, so that the assignment of the terminating isotope to a certain atomic number and, therewith, the end of the decay chain was eventually unclear [5]. The first problem had been solved by measuring the -spectra and SF events of a representative sample again 3 years after the experiment and demonstrating the absence of any possible actinide contamination [6].…”
Section: Introductionmentioning
confidence: 99%
“…The alpha spectra revealed the presence of Am, Cm and Po isotopes, the latter presumably produced by transfer reactions on Pb impurities in the target or target backing. A Dubna study of one 2-year-old counting sample by Dressler et al [28] found alpha activity due to some americium isotopes but no evidence of spontaneous fission activity during very long counting times. Despite separations designed to occlude interferences, the extraordinarily low event rates and as yet not perfected chemistries counsel the need for extreme caution in the face of uncertain chemical purity.…”
Section: Z = 115mentioning
confidence: 97%
“…During this experiment 15 SF events were detected that could be attributed to decay products of 288 115 based on long-term spectrometric analysis of a final sample [9]. Within a second experiment designed to isolate Db, a LaF 3 precipitation followed by either anion or extraction chromatography was used instead of cation exchange.…”
mentioning
confidence: 99%